Effects of Different Storage Methods on Fresh Macadamia Nut Quality - Jiarong FU; Yuanmiao WEI; Wenting XU; Shangxuan MA; Xiaojing HU; Yuwen WANG; Kechang HUANG; Gangjun GUO; Xiyong HE (Shipin gongye ke-ji)
The fresh macadamia nuts were stored by 3 storage methods: field spreading storage, indoor spreading storage, and indoor stacking storage for 70 days. Differences in environment temperature, pile temperature, moisture content, cracking rate, mold rate, nut-in-shell moisture content and color, kernel moisture content, defective kernel rate, malondialdehyde content, total phenol content, total sugar content, acid value, peroxide value, iodine value, and DPPH radical scavenging ability were monitored during storage, and correlation and principal component analyses were performed. During storage, the water content of nuts in indoor spreading storage initially decreased, then stabilized. By contrast, water content of nuts in indoor stacking and field spreading storage did not undergo consistent change. During the storage period, the moldy fruit rate reached 100% after 30 d of indoor stacking, 40 d of indoor spreading, and 60 d of field spreading. The macadamia nut kernel defect ratio at day 70 of storage was 23.33% for indoor spreading, 20.67% for field spreading, and 49.33% for indoor stacking. The respective malondialdehyde contents were 1.03, 1.18 and 1.01 mg/kg; acid values were 114.30, 105.70 and 119.53 μg/g; peroxide values were 135.88, 94.92 and 126.90 μg/g; iodine values were 681.74, 658.67 and 656.88 mg/g; total phenol contents were 1.43, 1.54 and 1.69 mg/g; and total sugar contents were 199.12, 201.04 and 200.14 mg/g; DPPH radical scavenging rates were 96.10%, 97.77% and 99.50%. Correlation analysis showed significant positive pairwise correlations (P<0.05) between kernel defect ratio, total phenol, total sugar, malondialdehyde, peroxide value, and acid value. Defective nut rate and DPPH radical scavenging rate were also significantly positively correlated (P<0.05). The iodine value was significantly negatively correlated with total phenol, total sugar, malondialdehyde, peroxide, acid value, and defective nut rates (P<0.05). The contribution rates of PC1 and PC2 in PCA were 87.7% and 4.7%, respectively, and the quality difference between 3 storage methods after 10 days was small. Indoor spreading should be used for storage for more than 10 days. Based on the changes in defective nut rates of different storage methods, the order of storage methods was indoor spreading, field spreading, and indoor stacking. This study provides a methodological reference for quality preservation and loss reduction in fresh macadamia nuts.